Sources of information on diabetes and its demographic correlates: a nationwide survey among Singapore residents. (26th October 2022) - Subramaniam, Mythily; Lau, Jue Hua; Asharani, P V; Abdin, Edimansyah; Roystonn, Kumarasan; Wang, Peizhi; Devi, Fiona; Vaingankar, Janhavi Ajit; Car, Lorainne Tudor; Sum, Chee Fang; Lee, Eng Sing; van Dam, Rob M; et al.
Summary: Diabetes is a major public health concern in Singapore, and the Singapore Government declared a 'War on Diabetes', which included a nationwide public health campaign. It is important to identify what sources of diabetes information reach the general population, whether this differs by socio-demographic characteristics and if the sources of information influence knowledge of diabetes to aid the successful dissemination of health information. Two thousand eight hundred ninety-five respondents were part of a population-based cross-sectional study conducted from February 2019 to September 2020. Respondents rated on a five-point scale whether they had obtained information on diabetes from eight different information sources, and responses were dichotomized into 'endorsed receiving information' or 'not endorsed receiving information'. Poisson regression models were conducted with the 'endorsement of receiving information' from each source as the outcome and socio-demographic variables as predictors. 95.9% of the study population had received information on diabetes from at least one source, and the mean number of sources was 4.2 ± 2.0. The leading source was media articles (82.1%), followed by health promotion videos/advertisements (77.9%), online websites (58.5%), books (56.5%), healthcare professionals (55.0%), radio (54.4%), public forums (27.7%) and support groups (15.5%). Endorsing a greater number of informational sources was associated with being younger, belonging to Malay or Indian instead of Chinese ethnicity, and having diabetes. An intensive nationwide diabetes awareness campaign successfully reached the public in Singapore with specific sources of information depending on socio-demographic characteristics. Findings suggest that diabetes information campaigns should utilize multiple channels for dissemination considering the different socio-demographic subgroups.